Al Capone does my shirts - Choldenko, Gennifer 1957- (Putnam, 2004)
A twelve-year-old boy named Moose moves to Alcatraz Island in 1935 when guards' families were housed there, and has to contend with his extraordinary new environment in addition to life with his autistic sister.